2020
DOI: 10.1111/sms.13766
|View full text |Cite
|
Sign up to set email alerts
|

Temporal aspects of affective states, physiological responses, and perceived exertion in competitive cycling time trials

Abstract: Athletes’ affective states can vary dramatically before, during, and after competition. Further, intense affect is associated with physiological responses that may amplify biological reactions manifested from the execution of physical tasks underlying performance. Fluctuations in perceptual cues (eg, perceived exertion) and physiological responses (eg, blood lactate, heart rate) can influence performance and vary dramatically in relation to competition. However, the pattern of these fluctuations and potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…At a time of decision making, the recall of affective experience from exercise is likely to be an important factor to construct the anticipatory affective states. Previous study shows that individuals who anticipate a more pleasant affective experience from exercise report higher, positive affective responses during the subsequent exercise trials (Davis and Stenling, 2020). Findings obtained from the present study raise important applied implications for professionals aiming to optimize health and high performance as well as the development of training programs designed to maximize exercise adherence.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…At a time of decision making, the recall of affective experience from exercise is likely to be an important factor to construct the anticipatory affective states. Previous study shows that individuals who anticipate a more pleasant affective experience from exercise report higher, positive affective responses during the subsequent exercise trials (Davis and Stenling, 2020). Findings obtained from the present study raise important applied implications for professionals aiming to optimize health and high performance as well as the development of training programs designed to maximize exercise adherence.…”
Section: Discussionsupporting
confidence: 54%
“…The remembered affective experience of physical activity has been noted to influence the anticipated affective responses to subsequent sessions of physical activity (Kwan et al, 2017;Davis and Stenling, 2020). Although this observation is important for physical activity promotion, a limitation that arises from the aforementioned studies relates to the timing of the post-exercise measurement of remembered affective experience.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, negative automatic associations with exercise act as a restraining force toward future exercise engagement (Brand & Cheval, 2019). In line with the ART, affective responses to episodes of physical activity have been found to predict concurrent and future physical activity behavior (e.g., Davis & Stenling, 2020;Williams et al, 2012).…”
Section: Dual-process Modelsmentioning
confidence: 67%
“…Learned responses are also likely to affect forecasted pleasure (how pleasant or unpleasant one anticipates exercise to be). Remembered and forecasted pleasure are typically linked; how one recalls an exercise session is presumed to influence anticipated affective responses to subsequent exercise sessions (e.g., Davis & Stenling, 2020). Zenko et al (2016) observed strong positive associations of remembered pleasure and subsequent forecasted pleasure assessed at 15 min (r = .84), 24 hours (r = .86), and 7 days (r = .88) following an exercise bout.…”
Section: Affective Responses To Exercisementioning
confidence: 99%
“…Across the duration of a sport event, athletes must endure compounding psychophysiological demands which can influence perceptual and physiological responses that may negatively impact upon performance. 1,2 The cumulative effects of exertion and physiological responses (e.g., blood lactate), derived from the management of physical load athletes contend with during performance, can manifest implications for perceptual-cognitive components of sport performance (e.g., aiming in biathlon). 3,4 However, limited research has investigated how physiological responses, affective states, and exertion may influence cognitive and physical sport performance both independently and simultaneously.…”
Section: Introductionmentioning
confidence: 99%